Use of Main Components and Data Envelopment Analysis to Evaluate the Efficiency of Water Operators - Sanchez Velasco, José (IJRDO-Journal of Applied Science, 2018)
The purpose of this work is to analyze the efficiency of Water Operator Organizations of México from the premise that each operator organization is in different working conditions and evaluated from different performance indicators, so obtaining efficiency for each organism could ambiguously arise in this regard, this manuscript paper provides from analysis of generalized variables and their relationship with factors of operation those variables that influence the efficiency process. This document is based on a free database from the Program of Indicators of Management of Operative Organizations (PIGOO in spanish), which initially involves 139 municipal water systems throughout the Mexican Republic. The result highlights the influence of certain variables in the performance of the operation of water systems, according to this, the usefulness of this work is expected to contribute by defining elements that improve the competitiveness of the aforementioned organizations.